Relaxing credit constraints in emerging economies: The impact of public loans on the performance of Brazilian manufacturers - Gianmarco I. P. Ottaviano; Filipe Lage de Sousa (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Especially in developing countries credit constraints are often perceived as one of the most important market frictions constraining firm innovation and growth. Huge amounts of public money are being devoted to the removal of such constraints but their effectiveness is still subject to an intense policy debate. This paper contributes to this debate by analysing the effects of the Brazilian Development Bank (BNDES) loans. It finds that, before receiving BNDES support, granted firms are indeed more credit constrained than comparable non-granted firms. It also finds that BNDES support allows granted firms to achieve the same level of performance as similar non-granted firms that are not credit constrained. However, it does not allow granted firms to outperform similar non-granted ones.
Keywords: O38; H00; 330; heterogeneous firms; productivity; public policy analysis; credit constraints